2016
DOI: 10.4049/jimmunol.1600143
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Th1-Biased T Follicular Helper (Tfh) Cells in Lymphoid Tissues during Chronic Simian Immunodeficiency Virus Infection Defines Functionally Distinct Germinal Center Tfh Cells

Abstract: Chronic HIV infection is associated with accumulation of germinal center T follicular helper cells (GC-Tfh) in the lymphoid tissue. The GC-Tfh cells can be heterogeneous based on the expression of chemokine receptors associated with T helper lineages such as CXCR3 (Th1), CCR4 (Th2), and CCR6 (Th17). However, the heterogeneous nature of GC-Tfh cells in the lymphoid tissue and its association with viral persistence and antibody production during chronic SIV/HIV infection is not known. To address this, here we ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 56 publications
(107 reference statements)
9
124
0
Order By: Relevance
“…Recently, others and we reported an aberrant accumulation of virus-infected Tfh cells in the lymph nodes (LNs) and rectal mucosa of SIV-infected RMs with high viral load (VL) (14,15,(24)(25)(26)(27), which was not evident in vaccinated SIV-infected RMs with low VL during a pathogenic SIVmac251 infection (15). In the current study, we sought to understand the role of antiviral CD8 T cells in limiting the virus-infected Tfh cells.…”
mentioning
confidence: 99%
“…Recently, others and we reported an aberrant accumulation of virus-infected Tfh cells in the lymph nodes (LNs) and rectal mucosa of SIV-infected RMs with high viral load (VL) (14,15,(24)(25)(26)(27), which was not evident in vaccinated SIV-infected RMs with low VL during a pathogenic SIVmac251 infection (15). In the current study, we sought to understand the role of antiviral CD8 T cells in limiting the virus-infected Tfh cells.…”
mentioning
confidence: 99%
“…For example, many studies have demonstrated that T H 1 cells maintain flexibility with the T FH cell type (19, 30, 48). More recently, there have also been reports of T H 1-biased T FH cell populations (49, 50). Corroborating these studies, our laboratory has previously demonstrated that T H 1 cells are capable of upregulating a Bcl-6-dependent T FH -like cell state in response to altered IL-2 signaling (28, 30).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, following immunization with influenza vaccines (19) or HPV vaccines (20) (i.e., during more limited antigen exposure), humoral immune responses were correlated with CXCR3 + CXCR5 + PD-1 + CD4 + T cells, and CXCR3 + CXCR5 + CD4 + T cells were also observed in blood and lymph nodes in rhesus macaques immunized with an SIV vaccine (21). In addition, recent studies in non-human primate models also reported induction of CXCR3 + Tfh in chronic SIV infection (22). Therefore, the contribution of pTfh subsets to the development of protective Ab responses seems to be context dependent and requires further investigation.…”
Section: Introductionmentioning
confidence: 82%